Efficient spin excitation via ultrafast damping-like torques in antiferromagnets - Christian Tzschaschel (Nature Portfolio, 2020)
Spin damping plays a fundamental role in many areas of spintronics, however, it is typically assumed that damping is irrelevant for impulsive spin excitations due to their rapid timescale. Here, the authors demonstrate that damping leads to a large and immediate spin-canting in anti-ferromagnets.